2017
DOI: 10.1177/1029864917697783
|View full text |Cite
|
Sign up to set email alerts
|

What is ‘open-earedness’, and how can it be measured?

Abstract: Recent years have seen some fundamental changes in the study of responses to music: the growth of neuroscientific approaches, in particular, is throwing new light on the role of imagination, affect and emotion. One focus has been on the nature of musical preferences in relation to other affective and cognitive judgements, and another has been on the issue of changes in musical preference across the lifespan. One explanatory concept which has proved useful in this respect is that of 'open-earedness', first form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
(55 reference statements)
2
9
0
Order By: Relevance
“…With a sample of more than 4,000 adults, we have found that age trends in musical taste were relatively similar when measured with music genres and with extracts of audio-recordings (music clips). The age trends revealed in this investigation mostly replicated the trends found in past research (Bonneville-Roussy et al, 2013), confirming the validity of the age trends, and broadly speaking, the assumption that musical preferences might not be fixed in adulthood (Bonneville-Roussy et al, 2013; Bonneville-Roussy et al, 2017; Greasley & Lamont, 2006; Hargreaves & Bonneville-Roussy, 2018; Hemming, 2013; North, 2010). In a nutshell, we have found three main age trends in musical preferences: an upward trend composed of the Jazzy and Unpretentious dimensions that were increasingly liked with age, a stable trend with the Classical dimension, and a downward trend, composed of the Contemporary and Intense dimensions, that were gradually more disliked with age.…”
supporting
confidence: 85%
“…With a sample of more than 4,000 adults, we have found that age trends in musical taste were relatively similar when measured with music genres and with extracts of audio-recordings (music clips). The age trends revealed in this investigation mostly replicated the trends found in past research (Bonneville-Roussy et al, 2013), confirming the validity of the age trends, and broadly speaking, the assumption that musical preferences might not be fixed in adulthood (Bonneville-Roussy et al, 2013; Bonneville-Roussy et al, 2017; Greasley & Lamont, 2006; Hargreaves & Bonneville-Roussy, 2018; Hemming, 2013; North, 2010). In a nutshell, we have found three main age trends in musical preferences: an upward trend composed of the Jazzy and Unpretentious dimensions that were increasingly liked with age, a stable trend with the Classical dimension, and a downward trend, composed of the Contemporary and Intense dimensions, that were gradually more disliked with age.…”
supporting
confidence: 85%
“…Two further listener-related factors (beyond Familiarity , Style Preference , and Expertise ) have not been considered in this study, yet they probably have a considerable impact on groove: listeners’ positive attitude to dancing (or other activities that require bodily entrainment) is likely to coincide with a strong groove response, as shown by Witek et al [ 5 ]. And listeners’ open-earedness [ 117 ] might be relevant as well: open and curious listeners will probably be more responsive to previously unknown music than narrow-minded listeners.…”
Section: Discussionmentioning
confidence: 99%
“…However, the crystallisation hypothesis has exclusively focused on popular music and the “greatest hits” and has failed to take into account the breadth of musical genres that individuals might listen to. Recent advances in music psychology research have shown that musical preferences, measured with various genres and styles, might keep developing up until much later in adulthood, perhaps even develop throughout the entire lifespan (Bonneville-Roussy et al, 2013; Bonneville-Roussy et al, 2017; Greasley & Lamont, 2006; Hargreaves & Bonneville-Roussy, 2018; Hemming, 2013; North, 2010), thereby confirming a hypothesis put forward by Hargreaves (1982) and Leblanc, Sims, Siivola, and Obert (1996). The question remains open whether the possible changes in musical preferences across the lifespan are influenced by the actual contents of the music.…”
Section: Intrinsic Properties Of the Music As Determinants Of Musicalmentioning
confidence: 99%